Designning Informatics Learning Media For Class VII Using Articulate Storyline 3 at SMPN 4 Bukittinggi - Nabila, Tuti; Musril, Hari Antoni; Okra, Riri; Derta, Sarwo (BiCED Proceeding, 2023)
This research is motivated by problems at SMPN 4 Bukittinggi. From the results of interviews with teachers and students, it was found that informatics subjects still used simple teaching methods such as blackboards, books, and concept maps. This study aims to increase the efficiency of the learning process by designing computer teaching materials using Articulate Storyline 3. Researchers used the development method or research and development (R&D) in designing class VII computer learning materials at SMPN 4 Bukittinggi. The development approach used is Planning, Production, and Evaluation (PPE). From the results of the study, the researcher succeeded in designing computer teaching materials using three articulation scenarios. This teaching material can be used by teachers and students in computer science subjects. The validity test was carried out by involving four validators, and an average value of 0.83 was obtained which indicated a good level of validity. The practicality test was carried out by three examiners, and an average value of 0.89 was obtained which indicated a high level of practicality. The effectiveness test was carried out by one subject teacher and 26 students, and an average value of 0.85 was obtained which indicated a high level of effective.